OP12 Understanding perspectives on major service changes: Exploring the development and communication of arguments for and against system reconfiguration. (13th September 2016) - Foley, C; Droog, E; Healy, O; Buckley, C; Boyce, M; Browne, JP
Abstract : Background: A series of urgent and emergency care system reconfiguration programmes have recently been implemented in several regions across Ireland. Changes have included the transfer of emergency care from small, rural hospitals to larger, typically urban-based hospitals. Programme planning documents state that changes are designed to improve patient safety and system efficiency, while preserving access to services. This view has been openly contested by members of the public, politicians and some clinicians, with organised opposition groups established to fight against service changes. This study examines the construction of arguments advocating reconfiguration, how they were communicated to the public and the development of opposing narratives. Methods: Two qualitative methods were employed. Documentary analysis was used to explore the development of reconfiguration policy and its manifestation in programme planning documents. Semi-structured interviews were conducted with 198 purposively sampled internal and external stakeholders across eight regions. Internal stakeholders included healthcare planners, managers and clinical staff. External stakeholders included politicians, campaign group members and patient representatives. Framework analysis was used, integrating inductive and deductive approaches. The analysis was informed by theories of risk perception and communication. Results: There is evidence of path dependence across policy documents, with plans developed on the basis of existing structures rather than population need. Implementation planning documents provide limited detail on public engagement and communication strategies. Among interviewees, those in favour of change typically endorsed arguments presented by policy documents. Those opposed to reconfiguration drew on broad narratives around austerity and rural decline, however local concerns predominated. For these participants risk was primarily described in terms of increased distance to acute hospital care, and planned trade-offs to preserve access were rejected. The local nature of opposition was reflected in failed attempts to form a national platform to fight reconfiguration. Conclusion: Policy and planning documents emphasise the risks of failing to change but provide little detail on public engagement. Those opposed to changes expressed scepticism regarding the stated goals of reconfiguration programmes, arguing they addressed organisational concerns at health service and governmental level rather than the needs of service users in their particular locality. Policy makers must engage with public concerns at a local level throughout the planning and implementation of system reconfiguration rather than offering generic justifications for change.